Enhancing Students' Comprehension Skills: Development of Flipped Classroom Teaching Materials for English Correspondence Learning - Rr Sri Kartikowati; Dewi Nurmalasari; Eka Dewi Utari; Ria Rahma Nida; Ferry Setyadi Atmadja; Bayu Suhendry; Mayang Riyantie (Nurul Jadid University, 2025)
This study aims to develop flipped classroom-based teaching materials to enhance students' comprehension skills in English Correspondence, a critical course for fostering professional written communication in international business contexts. The research used a Research and Development (R&D) approach, specifically the 4D model (Define, Design, Develop, Disseminate). Expert validation of the materials yielded a high validity score of 86%. A small-group trial yielded an 84% practicality score, indicating the usability of the materials. Effectiveness was measured through a pretest and posttest, revealing a moderate improvement in student comprehension with an N-gain score of 0.54. These findings suggest that the flipped classroom model enhances students' engagement, supports independent learning, and strengthens both theoretical and practical understanding of English business correspondence. The developed materials demonstrate the potential of flipped classrooms in improving comprehension skills and learning outcomes in English Correspondence courses. This research highlights the practical implications of innovative teaching strategies in higher education.